Book Review: How Solidarity Works for Welfare - Singh, Prerna (Penerbit Universiti Sains Malaysia (USM Press), 2018)
Prerna Singh’s book comes with some trailing glory: It won the 2016 Woodrow Wilson Foundation Award of the American Political Science Association, and was also a co-winner of the 2016 Barrington Moore Book Award of the American Sociological Association. It deals with some important questions: Why do some Indian states have better social service provision and welfare outcomes than others? What are the conditions that promote social welfare? What best explains the stark variations in educational and health outcomes within India? How might it be possible to improve outcomes in laggard states such as Rajasthan, Uttar Pradesh and Bihar towards those achieved by Tamil Nadu and Kerala? The comparisons between these three north and two south Indian states are well known to economists, public health specialists and educationalists, but there are few good explanations out there that try to account for these differences. In the feld of political economy, one of theseincreasingly challengedis that public goods are less likely to be delivered in settings of social diversity, as indicated by caste, religion or ethnicity. Singh’s contribution to the debate is that “subnational solidarity fosters a sense of collective welfare, promotes political awareness and participation, and encourages popular monitoring of public goods” (55).